Empipe3D™ User’s Manual Version 4.0 -- UNIX - Bandler, John W.; Optimization Systems Associates; Biernacki, R.M.; Chen, S.H. (Optimization Systems Associates, 1997)
Empipe3D™ is a powerful and friendly software system for automated electromagnetic (EM) design optimization, driving the 3D field solvers Ansoft HFSS and HP HFSS. Ansoft HFSS and HP HFSS are finite element based solvers for full-wave EM field analysis of three dimensional passive structures. They are capable of computing S-parameter responses, electromagnetic field distributions and radiative effects at microwave frequencies. Empipe3D allows you to designate geometrical and material parameters as candidate variables for optimization in an intuitive and friendly manner. Using the 3D graphical drawing tool within the HFSS package, you create a set of incremental changes to the solid model. The information is then processed by Empipe3D to parameterize the structure using OSA's exclusive Geometry Capture technology. Empipe3D employs the sophisticated optimizers in OSA90, a program supplied as part of the Empipe3D package. OSA90 offers a comprehensive set of optimizers, including L1, L2 (least squares), minimax, Huber, quasi-Newton, conjugate gradient, simplex, simulated annealing and random algorithms, with proven track records in engineering applications. OSA90 also offers a wealth of options for mathematical expressions, response postprocessing, statistical analysis and yield optimization, as well as many graphical display and visualization formats.
Empipe3D is a powerful and friendly software system for automated electromagnetic (EM) design optimization, driving the 3D field solvers Ansoft HFSS and HP HFSS. Empipe3D runs on PC platforms under Windows 95® and Windows NT®, and on UNIX workstations: Sun, Hewlett-Packard and DEC under X-Windows. This yellow covered manual deals with the UNIX installations.
Keywords: Empipe3D; HP HFSS; Ansoft HFSS; Maxwell Eminence; Optimization Systems Associates; full wave; electromagnetic optimization; microwaves; L1, L2, minimax, Huber optimization; OSA90; Geometry Capture; Datapipe; parameterization; finite elements